MAKING WEBSITE VOCATIONAL HIGH SCHOOL (SMK) BINA PUTRA USING MACROMEDIA DREAMWEAVER MX 2004 - Hary Rahmansyah; Ristyawati, SKom,MMSI Ristyawati, SKom,MMSI (Jurnal Sistem Informasi, 2008)
World of technology in Indonesia is currently very rapid, especially in informationtechnology and information society will also need a fast, accurate, and actual isneeded by society at large.Lots of media information, the authors chose the Internet information media whichhas been a subject matter in this writing. Scientific writing about the design of thewebsite explains information about the Vocational Secondary School (SMK) BinaPutra using Macromedia Dreamweaver MX Application Program, the author willexplain how the process of designing and preparing the documents in a "VocationalHigh School website (CMS) Bina Putra" allowing you to easy to understand theintent and purpose built website.